Sibutramina: failed and incomplete documents on prescription and dispensing - de Souza, Syliana Sana Silva; Pinheiro, Mirian Talita Reis Santos; Almeida, Paulo Henrique Ribeiro Fernandes; Lemos, Lucas Brasileiro; Lemos, Gisele da Silveira (Journal of Health Care, 2017)
Introduction: Sibutramine is currently the only drug used for the treatment of obesity with registration in Brazil. The requirements for its prescribing and dispensing increased with the Resolution No. 52, which entered into force in December 2011. Objective: To evaluate the impact of this resolution on the commercialization of the product as well as failures and mistakes in the process of prescribing and/or dispensing it in a community pharmacy. Methods: We analyzed 741 reports of sibutramine revenue and 258 terms of prescribing responsibility, retained in the community pharmacy, reffering to the period from January 2010 to June 2014. These documents were reviewed for completeness and readability of the required data in accordance with current laws in Brazil and grouped into two periods: before (1) and after (2) the Resolution No. 52. Results: Results show a statistically significant increase in completeness, with reduction of failures, from the first to the second period (p
Keywords: Sibutramine; Obesity; Community Pharmacy